2012
DOI: 10.1103/physrevb.86.075418
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of HgTe quantum wells

Abstract: Using analytical formulas as well as a finite-difference scheme, we investigate the magnetic field dependence of the energy spectra and magnetic edge states of HgTe/CdTe-based quantum wells in the presence of perpendicular magnetic fields and hard walls for the band-structure parameters corresponding to the normal and inverted regimes. Whereas one can not find counterpropagating, spin-polarized states in the normal regime, below the crossover point between the uppermost (electronlike) valence and lowest (holel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 46 publications
3
81
2
4
Order By: Relevance
“…Graphene-based double-layer devices can be used to observe Coulomb drag between massless and massive particles by coupling Dirac fermions in monolayer graphene to quasiparticles with parabolic dispersion in either bilayer graphene (Scharf and Matos-Abiague, 2012) or a usual 2DEG Scharf and MatosAbiague, 2012). Experimental realizations were reported in Fisichella et al (2014) and Gamucci et al (2014).…”
Section: Drag Between Massless and Massive Fermionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene-based double-layer devices can be used to observe Coulomb drag between massless and massive particles by coupling Dirac fermions in monolayer graphene to quasiparticles with parabolic dispersion in either bilayer graphene (Scharf and Matos-Abiague, 2012) or a usual 2DEG Scharf and MatosAbiague, 2012). Experimental realizations were reported in Fisichella et al (2014) and Gamucci et al (2014).…”
Section: Drag Between Massless and Massive Fermionsmentioning
confidence: 99%
“…Theoretical analysis of Principi et al (2012) and Scharf and Matos-Abiague (2012) is based on the standard expression (77). Both works focus on the low-temperature, degenerate regime T µ.…”
Section: Drag Between Massless and Massive Fermionsmentioning
confidence: 99%
“…Substantial efforts have been directed towards the investigation of the linear response of doped graphene 24 and of the charge density excitations [25][26][27][28][29] and of such complex quasiparticles as plasmarons 30,31 and plasmon-phonon complexes 32 . Recently, the experimental realization of graphene double-layer structures coupled only via the Coulomb interaction [33][34][35][36][37][38] has attracted substantial theoretical interest in studying the double-layer plasmon effects [39][40][41][42] and the frictional drag 43 in two spatially separated graphene layers [44][45][46][47][48][49][50][51][52] as powerful tools for probing interaction effects of massless Dirac fermions.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] The effect of external magnetic fields have also been considered. 6,8,[19][20][21][22][23][24] The TI state in HgTe QWs was predicted by Bernevig, Hughes, and Zhang (BHZ) 25 by using a simplified k · p model containing states with S-and P -like symmetries, respectively. They found that beyond a critical thickness of the HgTe QW, the TI state would appear as confirmed experimentally.…”
Section: Introductionmentioning
confidence: 99%